Pengaruh Viral Marketing, Kepercayaan dan Online Customer Reviews Terhadap Keputusan Pembelian Melalui Electronic Commerce yang Terdaftar Pada Indonesian E-Commerce Association di Gresik - Wachid, Ahmad Iqbal; Sukaris, Sukaris (Jurnal Mahasiswa Manajemen, 2022)
Background - The purchase decision is a very important factor for the existence and development of the company's business. Viral Marketing strategies are often used by companies to market their products through internet access. Not all consumer trust in information that is disseminated electronically can be guaranteed to be true. Information can be obtained from reviews or responses that have been given by consumers who have purchased the product. Objective - This study aims to determine the effect of viral marketing, trust and online customer reviews on purchasing decisions through electronic commerce registered with the Indonesian E-Commerce Association in Gresik. Design/Methodology/Approach - The population in this study are people who use and shop through e-commerce in Kebomas District. This study uses quantitative research, saturated sampling technique and uses probability sampling methods with the number of samples are 154 respondents. Findings - The result of this research is proven that the variables of Viral Marketing, Trust and Online Customer Reviews have a significant effect on purchasing decisions through Electronic Commerce which are registered in the Indonesian E-Commerce Association in Gresik. Research implications - This research can be used as additional information for e-commerce companies related to marketing management in improving purchasing decisions. Research limitations - This research is only conducted on people who use and shop through e-commerce in Kebomas District.